Frasa Nominal Bahasa Nambla (Tukuih) - Yohanis Sanjoko (Gramatika: Jurnal Ilmiah Kebahasaan dan Kesastraan, 2013)
This paper discusses about noun phrase in Nambla language (Tukuih). Noun phrase is aphrase which has same distribution as noun. The objective of this paper is to describe the patterns of noun phrase of Nambla language, kinds of word classes which fill into attribute constituent, word class sequences which fill into attribute constituent and correlation of meaning between nucleus constituent and attribute one. This paper uses descriptive method which includes collecting data, analyzing data and presenting the result of data analysis. In collecting the data, the researcher uses conversational method by stimulating technique as a basic technique and face to face conversation technique and noting technique as the advance technique. in analyzing the data, the researcher uses distributional method. General patterns of noun phrase of Nambla language is DM. Noun phrase of Nambla language consist ofnucleus constituent which is always filled by noun and attribute constituent which can befilled by noun, pronoun, adjective, determiner, numeral, and relative clause. Some relations of meanings which emerge as a result of this syntax process are possessive meaning, locative,qualitative, quantitative, deictic and description.